Generation Z work-life preferences: Organizational, social, and arrangement effects - Adhiati, Cheesya Siska; Palupiningtyas, Dyah; Samtono, Samtono (Goodwood Publishing, 2025)
Purpose: This study aims to examine the influence of organizational and social environmental factors on Generation Z's work-life balance (WLB) preferences in Semarang City, with work arrangements as a moderating variable. Methodology: Using a quantitative explanatory design, data were collected from Generation Z employees in the creative, technology, and public service sectors through stratified purposive sampling. Moderated regression analysis (MRA) was employed to test the hypotheses. Results: The research results indicate that organizational factors exert a positive influence on Generation Z's work-life balance preferences. Furthermore, the social environment is also shown to have a positive effect on these preferences. Additionally, work arrangements significantly moderate the relationship between organizational factors and work-life balance preferences, as well as the relationship between the social environment and work-life balance preferences. Conclusion: The study highlights the critical role of work arrangements in shaping Generation Z’s WLB preferences. Organizations should develop adaptive HR policies and flexible work options to better align with their expectations. Limitations: The study is limited to Semarang City and specific sectors, which may affect generalizability. Self-reported data could also introduce bias. Contribution: This research extends WLB literature by integrating Social Exchange Theory and Boundary Theory while offering practical insights for organizations to enhance workforce strategies for Generation Z.